Catalysts Based on Ni and Mg Oxides for the One-Pot Production of High Added-Value Products from Furfural. - Maderuelo-Solera, Rocío; Jiménez-Gómez, Carmen Pilar; Cecilia-Buenestado, Juan Antonio; García-Sancho, Cristina; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (Wiley, 2024)
A family of NiO-MgO samples with Ni/Mg molar ratio between 0.10 and 0.30 are synthesized by co-precipitation and subsequent calcination. The characterization of the samples show the formation of a solid solution with a periclase structure in such a way that the Ni2+species are poorly reducible. After the reduction of the NiO-MgO samples at 500 °C, the catalysts are tested in the furfural (FUR) hydrogenation to obtain valuable products in a one-pot reaction. The catalysts are highly selective toward tetrahydrofurfuryl alcohol (THFA) with a yield above 50% in most cases as well as 1,2-pentanediol (1,2-PeD) and 1,5-pentanediol (1,5-PeD) with maximum yield of 22 and 23% after 22 h of reaction at 170 °C and 4 MPa of H2, respectively. The present work also suggests the presence of two routes in the furfuryl hydrogenation. The first one is associated with the reduction of furfural to furfuryl alcohol (FOL) and the hydrogenation of the ring yielding THFA. In the second route, once FOL is formed, the furanic ring is open to form 1,2-PeD and 1,5PeD.
Keywords: Catalizadores; Química verde; Reacciones químicas; Catalysts; Furfural hydrogenation